2010
DOI: 10.1007/978-3-211-99651-5_26
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative CT in Spine Surgery

Abstract: Intraoperative CT is a useful tool to check the correct position of the implants used, the extent of decompression and the realignment as early as possible. It therefore reduces second operations. A postoperative CT is no longer necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…29 Unlike intraoperative mobile CT imaging associated with navigation, conventional CT for pedicular screw positioning is well documented. 32,33,37 A recent study on Airo CT-based navigation reported perforation rates of 6.8% for lumbar and 2.5% for thoracic screws and no misplaced screws (> 4 mm) in a sample of 137 screws. 8 Few studies have compared different navigation methods for pedicular screw positioning.…”
Section: Screw Accuracymentioning
confidence: 99%
“…29 Unlike intraoperative mobile CT imaging associated with navigation, conventional CT for pedicular screw positioning is well documented. 32,33,37 A recent study on Airo CT-based navigation reported perforation rates of 6.8% for lumbar and 2.5% for thoracic screws and no misplaced screws (> 4 mm) in a sample of 137 screws. 8 Few studies have compared different navigation methods for pedicular screw positioning.…”
Section: Screw Accuracymentioning
confidence: 99%
“…The first intraoperative CT was used by Shalit in 1978 [2]. Despite several reports on the benefits and usefulness of this method, intraoperative CT is not very common.…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
“…Studies have demonstrated that [ 13 , 14 ] when the stenosis rate of the spinal canal is over 50%, not only is the posterior longitudinal ligament damaged, but the fracture block protruding into the spinal canal is likewise overturned. With pedicle screws alone, it is hard to eliminate the fracture fragments in this type of fracture [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%